Human genetic engineering and social justice in South Africa: Moltmann and human dignity - M. Kotzé (Acta Theologica)
The realities of social injustice in the present South African context, with its great and growing gap between rich and poor and unequal distribution of wealth and resources, are also acutely visible in the health-care sector. Genetic engineering would lead to some children having the cards stacked overwhelmingly in their favour, raising the concern for the justice or fairness of this type of biotechnology. In this contribution, I argue that the notion of justice as fairness, put forward by Rawls, and the focus on human dignity in Moltmann’s theology can help address the bioethical challenges of genetic engineering in the context of inequality, specifically in South Africa.